The Phenomenon of Beauty in Fairy-Tales within the context of Ethical-Aesthetical Conceptions - Çiğdem Akyüz Öztokmak (Akademik Dil ve Edebiyat Dergisi, 2026)
Tales are formed orally by their nature and continue their existence for generations by maintaining their anonymous structure. Inspired by the power of the parole, story telling creates a visual memory through words, and it is thought to contribute to the formation of the individual's first aesthetic understanding. Aesthetic symbols designed for the child subject also serve the educational function and convey the first ethical information. It can be predicted that the individual, who has started to collect data on aesthetics in infancy, will acquire this as a skill in the continuation of his life. Aestheticized symbols used in fairy-tales are usually simple objects, colors, or concepts that children are familiar with and relatively easy to understand. In this study, ethical-aesthetic teachings related to child education in fairy-tales have been examined within the context of the phenomenon of beauty on the basis of Arthur Schopenhauer's views in Metaphysics of Beauty: Secrets of Art and Beauty. While the universe of the study are tales, the sample is composed of the tales in Pertev Naili Boratav's collection titled Az Gittik Uz Gittik (We went less, We went Far). According to the findings of the study, Arthur Schopenhauer’s philosophy of beauty and the conceptions of beauty in Boratav’s fariy-tales are in line with each other. Both of them associate beauty with metaphysics. Additionally in Boratav’s fairy-tales the values that signify family ties such as mother, father, sibling, and the importance of being good and virtuous are at the forefront of ethical teachings and ethical values were determined to be transferred with aestheticized items. From this point of view it is aimed to emphasize that the new approaches and methods related to education can benefit from aesthetic-ethical expression opportunities of fairy-tales.